Small Amazonian stingless bees: an opportunity for targeted cocoa pollination - Maia-Silva, Camila; Hrncir, Michael; Giannini, Tereza Cristina; Toledo-Hernández, Manuel; Imperatriz-Fonseca, Vera L. (Frontiers in Bee Science, 2024)
Cocoa (Theobroma cacao) is a multi-billion-dollar business. This tropical crop strongly depends on animal pollination for fruit development and seed production. The lack or inefficiency of natural pollinators in cocoa plantations has driven farmers to search for alternatives, such as laborious pollination by hand. A so far untested alternative, which has received increasing attention during the past couple of years, is targeted crop pollination through managed social bees. However, owing to the smallness of the flowers of T. cacao as well as structural barriers that impede large insects to access the stigma, only tiny bees may be a viable option for targeted cocoa pollination. In the present study, we asked whether small stingless bees (Apidae, Meliponini) could come into consideration as managed cocoa crop-pollinators, especially in shadowy agroforests. Among the 188 meliponine species native to the Brazilian Amazon region, which comprises an important portion of the center of origin of T. cacao, we selected 52 species based on morphological criteria (intertegular distance ≤ 1.4 mm; body length: 2.2 -6.0 mm). Important for cocoa production, some of these Meliponini have an ample geographic distribution, occurring both in the center of origin of T. cacao and beyond (centers of cocoa production in Brazil: Pará: 35 spp., Bahia: 10 spp.). Presumably all species may be active at illuminance levels below those found in heavily shaded cocoa plantations, at least at times when anthers show full dehiscence and during maximum receptivity of the stigma. The bees' potential to forage under reduced light regimes is corroborated by the finding that between 20 and 60 % of the naturally exploited food sources are understory vegetation, including herbs, subshrubs, shrubs, and lianas. Many of the selected Meliponini build their nests, at least facultatively, in tree cavities, which facilitates their transfer to rational hives and, hence, the use of managed colonies in directed crop pollination. Important next steps for validating the potential of these small stingless bees in targeted cocoa pollination should comprise detailed studies on their foraging behavior and olfactory learning capacities.